Peptidyl arginine deiminase inhibition suppresses arthritis via decreased protein citrullination in joints and serum with the downregulation of interleukin-6. Issue 6 (2nd November 2019) - Kawaguchi, Hoshimi; Matsumoto, Isao; Osada, Atsumu; Kurata, Izumi; Ebe, Hiroshi; Tanaka, Yuki; Inoue, Asuka; Umeda, Naoto; Kondo, Yuya; Tsuboi, Hiroto; Ishigami, Akihito; Sumida, Takayuki
Abstract: Objective : To explore the relevance of citrullinated proteins and anti-citrullinated protein antibodies (ACPA) via protein arginine deiminase (PAD) inhibition in peptide glucose-6-phosphate isomerase-induced arthritis (pGIA). Methods : Cl-amidine, a PAD inhibitor, was injected into pGIA. Clinical scores and histopathological findings of ankle joints were assessed. Serum ACPA titers were analyzed using ELISA. Citrullinated protein expression in joints and sera were examined with immunohistochemistry and Western blot analysis, respectively. Serum levels of IL-6, TNFα, and IL-1β were measured with cytometric bead array (CBA). Gene expression levels of IL-6 and TNFα in joints, lymph nodes, and spleens were analyzed with quantitative PCR. GPI-specific productions of IFNγ and IL-17 from T cells in lymph nodes were evaluated. Results : Cl-amidine treatment significantly reduced arthritis severity while ACPA titers tended to be lower, but not significantly different compared to the control. Citrullinated proteins in joints and sera from treated mice were clearly decreased. With Cl-amidine treatment, serum IL-6 levels were significantly decreased, and IL-6 and TNFα gene expression were significantly reduced in joints. IL-17 production from GPI-specific T cells tended to be lower in Cl-amidine-treated mice, but not significantly different. Conclusion : Our results suggested that PAD-mediated citrullinated protein was involved in the pathogenesis of arthritis via IL-6.